Book review: Anand Pandian, A Possible Anthropology: Methods for Uneasy Times. (November 2020) - Kawlra, Aarti
Anand Pandian, A Possible Anthropology: Methods for Uneasy Times . Duke University Press, 2019, 168pp., ₹2, 115, ISBN: 978-1-4780-0375-5 (paperback). ISBN:978-1-4780-0311-3 (cloth).